Micro-structural origin of elongation in swift heavy ion irradiated Ni nanoparticles: A combined EXAFS and DFT study. (December 2016) - Sarker, Debalaya; Bhattacharya, Saswata; Ghosh, S.; Srivastava, P.
Abstract: Aiming for perpendicular magnetic storage usage, shape anisotropy is introduced in Ni nanoparticles (NPs) embedded inside a thin SiO2 matrix using swift heavy ion irradiation (SHI). Systematic increase in NPs' aspect ratio along the direction of incident SHI beam is observed up to 5 × 10 13 ions/cm 2 (5e13) fluence from grazing incidence small angle X-ray scattering measurements. Strikingly, at higher fluences the major dimension (along SHI beam) got reduced. This observation is totally intriguing as usually particle elongation increases with applied fluence. To understand this anomaly, as a first step, we have performed a combined near and far edge X-ray absorption spectroscopy (XANES and EXAFS) analysis. This shows irradiated Ni NPs sustain their metallic phase even with increased structural disorder and reduced atomic co-ordination. However an atypical reduction in local structural anisotropy beyond 5e13 fluence is observed from angle dependent EXAFS: following the same trend as NP elongation. To have a better insight, the role of the electronic spin of individual atoms in controlling particle shape is investigated. Using the lattice temperature profiles derived from thermal spike model, we have carried out ab initio molecular dynamics (MD) simulations to understand the structural distortion at higher temperatures. The experimentally observed structural and shape anisotropy in the irradiated NPs is only realized when spin polarization contributions were considered in our calculations. From the pair correlation function and atom-wise spin density plots, we conclude that presence of spin affects the second co-ordination shell and controls the atomic arrangements in such a manner that elongated structures are preferred in the irradiated system at intermediate fluence (i.e. 5e13). Further increase in MD temperature to 6000 K (corresponding to 1 × 10 14 ions/cm 2 fluence) results in disordered spin alignment and melting of moderately weak spin polarized Ni NPs: thus violating conventional trend of increasing particle elongation w.r.t SHI fluence. Graphical abstract: